International Survey of Peer Leadership (ISPL): An Emerging Snapshot of the Status of Peer Leadership in South Africa (Journal of Student Affairs in Africa, 2021)
The power and importance of peer influence in educational settings has been well documented (Cuseo,2010; Ender & Kay, 2001; Keup, 2010). In South Africa, research supports international trends that student involvement in peer-led activities contributes to student success and ultimate throughput(Layton & McKenna, 2015; Loots, 2009; Underhill & McDonald, 2010). A plethora of research exists attesting to the benefits for students who are the recipients of peer-led activities. In South Africa, however, knowledge gaps exist pertaining to a national perspective on the experiences and, to someextent, on the benefits of peer leadership activities for peer leaders themselves. The purpose of this study is to provide an initial national snapshot of the development and experiences of peer leaders at six South African institutions of higher education, using the International Survey of Peer Leaders (ISPL).The research design adopted was a non-probability purposive sampling technique, with a sample size of N=466. Data were analysed using descriptive analyses. Findings validate previous findings and provide a more comprehensive picture of the types of peer leadership positions held, the trainingand support peer leaders receive, levels of engagement, and the benefits of being involved in peer-led activities.
Keywords: peer leadership; Higher education; student engagement; student involvement; peer leader development; peer leader gains; trends